Photoredox-Catalyzed Enantioselective α-Deuteration of Azaarenes with D2O - Shao, Tianju; Li, Yajuan; Ma, Nana; Li, Chunyang; Chai, Guobi; Zhao, Xiaowei; Qiao, Baokun; Jiang, Zhiyong (iScience, 2019)
The site-specific incorporation of deuterium (D) into small molecules is frequently used to access isotopically labeled compounds with broad utility in many research areas, such as drug development, mechanistic studies, and NMR analyses. Nevertheless, the deuteration of a stereocenter in an enantioselective manner, which could slow the metabolism and improve the bioavailability of bioactive molecules, remains challenging owing to the lack of established catalytic methods. Here, we report an asymmetric α-deuteration strategy for azaarenes with inexpensive D2O as the deuterium source. A cooperative visible light-driven photoredox and chiral Brønsted acid-catalyzed system using a Hantzsch ester as the terminal reductant has been developed, which enables racemic α-chloro-azaarenes and prochiral azaarene-substituted ketones to experience a single-electron reduction-enantioselective deuteration process. The transition metal-free method provides important chiral α-deuterated azaarenes in satisfactory yields with good to excellent enantioselectivities (up to 99% ee) and substantial deuterium incorporation.The site-specific incorporation of deuterium (D) into small molecules is frequently used to access isotopically labeled compounds with broad utility in many research areas, such as drug development, mechanistic studies, and NMR analyses. Nevertheless, the deuteration of a stereocenter in an enantioselective manner, which could slow the metabolism and improve the bioavailability of bioactive molecules, remains challenging owing to the lack of established catalytic methods. Here, we report an asymmetric α-deuteration strategy for azaarenes with inexpensive D2O as the deuterium source. A cooperative visible light-driven photoredox and chiral Brønsted acid-catalyzed system using a Hantzsch ester as the terminal reductant has been developed, which enables racemic α-chloro-azaarenes and prochiral azaarene-substituted ketones to experience a single-electron reduction-enantioselective deuteration process. The transition metal-free method provides important chiral α-deuterated azaarenes in satisfactory yields with good to excellent enantioselectivities (up to 99% ee) and substantial deuterium incorporation.